Technology Utilisation for Tax Acceleration: Training on the Use of PBB Application for Lempangang Village Residents - Nurhikmah; Al Ayyubi, Ibnu Imam; Prayetno, Eko; Muhaemin, Abdul; Permatasari, Indah (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2025)
This research discusses efforts to utilise technology to accelerate tax collection with a focus on training on the use of the Land and Building Tax (PBB) application for Lempangang Village residents. As part of the effort to increase public awareness and participation in tax payments, the training aims to provide practical knowledge on how to access, fill in, and report PBB obligations using digital applications that have been provided by the local government. By utilising technology, it is expected that the tax payment process will become more efficient, transparent, and easily accessible to the community, thereby contributing to increased local revenue and successful village development. The training involves villagers through a hands-on and interactive approach, and is expected to motivate them to be more active in fulfilling their tax obligations, which is one of the sources of funding for local development.